Return-Based Contrastive Representation Learning for Reinforcement Learning - Liu, Guoqing; Zhang, Chuheng; Zhao, Li; Qin, Tao; Zhu, Jinhua; Jian, Li; Yu, Nenghai; Liu, Tie-Yan (Ninth International Conference on Learning Representations(ICLR), 2021)
Recently, various auxiliary tasks have been proposed to accelerate representation learning and improve sample efficiency in deep reinforcement learning (RL). Existing auxiliary tasks do not take the characteristics of RL problems into consideration and are unsupervised. By leveraging returns, the most important feedback signals in RL, we propose a novel auxiliary task that forces the learnt representations to discriminate state-action pairs with different returns. Our auxiliary loss is theoretically justified to learn representations that capture the structure of a new form of state-action abstraction, under which state-action pairs with similar return distributions are aggregated together. Empirically, our algorithm outperforms strong baselines on complex tasks in DeepMind Control suite and Atari games, and achieves even better performance when combined with existing auxiliary tasks.